Critical Success Factors Of Supply Chain Manegement In Iranian Manufacturing Industry - Sadegh Teherian, Mohammad (2011)
In this thesis, researcher is going to study on critical success factors of supply chain management. Nowadays, supply chain management has become as a source of competitive advantages.